The Animality and Communio Creatorum: Kritik dan Tawaran bagi Teologi Kristen - Charlanency Bernabhita Meyok (Theologia in Loco, 2021)
This article attempts to criticize three main dimensions of Christian theology that are generally anthropocentric: incarnation theology, the concept of imago Dei, and ecclesiology. This article offers a new understanding of the three concepts by engaging with several theologians, namely Jaques Derrida, Neils Gregersen, Jürgen Moltmann, Lynn Towsend White, and some others theologians. The theology of the incarnation is reconstructed more broadly to interpret the incarnation not only for humans, but all creation. Furthermore, the idea of ​​Christ the Imago Dei and all creation created in the unique relationship of the Trinity is used as the key to declaring all creation as imago Christi and imago Trinitatis. These two reconstructions become the basis for correcting the concept of ecclesiology which tends to be anthropocentric. The main goal is to offer a cosmologically-based theological perspective that is not exclusive for humans, but inclusive for all creation—communio creatorum—the fellowship of all creations. Each with its uniqueness has an equal opportunity to glorify God. This article further provides alternative thoughts in dealing with the current ecological crisis.